Makna Persahabatan Dalam Lagu Kana Nishino “Best Friend” - Mugiyanti Mugiyanti; Candra Rizki Permana (IDEA : Jurnal Studi Jepang, 2021)
ABSTRACT: A song it is said to become popular if is known and loved almost throughout the world. Each song has different meanings and intentions, according to the purpose of the author. Kana Nishino is popular Japanese musician who create many hit songs in Japan. One of her songs which is she created “Best Friend" about friendship become popular song. That is the basis of the writer to research, analyze, and prove whether “Best Friend” has eight characteristics of friendship according to De Vito's theory. The author uses a descriptive method by examining the lyrics of “Best Friend” as well as the meaning of friendship. From this research indicate that the friendship shown in the song lyrics of Kana Nishino “Best Friend” has eight characteristics of friendship according to De Vito's theory.